Pengaruh Edukasi Manajemen Nyeri Persalinan Non Farmakologi Terhadap Tingkat Pengetahuan Ibu Hamil Trimester III di TPMB Kusnaenih - Nurul Hasna; Anjarwati Anjarwati; Sri Ratna Ningsih (Jurnal Sehat Indonesia (JUSINDO), 2026)
Labor pain is a natural physiological response caused by uterine muscle contractions during the first stage of labor. In Indonesia, 22% of women experience severe pain and 15% experience pain-related complications, yet 63% of them have never received education on labor pain management. Lack of education leads to mothers being less mentally prepared, leading to anxiety, stress, decreased self-confidence, and difficulty controlling emotions. This study aims to determine the effect of non-pharmacological labor pain management education on the knowledge level of pregnant women in the third trimester at the TPMB (Private Midwifery Practice) Kusnaenih. This study employed a quantitative method with a pre-experimental design approach. The sampling technique performed was a non-probability sampling technique with a total sampling rate of 46 respondents. Primary data were collected, and the Wilcoxon paired t-test was applied for data processing. The Wilcoxon paired t-test showed a significant difference between the pre-test and post- test group averages before treatment, with a p-value of 0.000 <0.005. The video-based education presented information clearly and systematically, making it easier for pregnant women to understand the material, which resulted in an increase in their knowledge level after the intervention. There is an effect of non-pharmacological labor pain management education on the knowledge level of pregnant women in the third trimester at TPMB Kusnaenih. TPMB Kusnaenih is recommended to hold classes for pregnant women as part of antenatal care, using the educational video from this study as one of the educational media.